2023
DOI: 10.1111/imb.12868
|View full text |Cite
|
Sign up to set email alerts
|

The spread of satellite DNAs in euchromatin and insights into the multiple sex chromosome evolution in Hemiptera revealed by repeatome analysis of the bug Oxycarenus hyalinipennis

Diogo C. Cabral‐de‐Mello,
Pablo Mora,
José M. Rico‐Porras
et al.

Abstract: Satellite DNAs (satDNAs) are highly repeated tandem sequences primarily located in heterochromatin, although their occurrence in euchromatin has been reported. Here, our aim was to advance the understanding of satDNA and multiple sex chromosome evolution in heteropterans. We combined cytogenetic and genomic approaches to study, for the first time, the satDNA composition of the genome in an Oxycarenidae bug, Oxycarenus hyalinipennis. The species exhibits a male karyotype of 2n = 19 (14A + 2 m + X1X2Y), with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In the genome of the Pacific oyster C. gigas we have revealed an unusual, highly scattered organization of relatively short satDNA arrays throughout the genome (Tunjić-Cvitanić et al 2021 ). Similarly, chromosomal mapping of satDNA in the insect Oxycarenus hialinipennis revealed its high spread in the euchromatic regions (Cabral-de-Mello et al 2023 ). These findings contradict the classical concept of satDNAs organization (as outlined in Introduction).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the genome of the Pacific oyster C. gigas we have revealed an unusual, highly scattered organization of relatively short satDNA arrays throughout the genome (Tunjić-Cvitanić et al 2021 ). Similarly, chromosomal mapping of satDNA in the insect Oxycarenus hialinipennis revealed its high spread in the euchromatic regions (Cabral-de-Mello et al 2023 ). These findings contradict the classical concept of satDNAs organization (as outlined in Introduction).…”
Section: Discussionmentioning
confidence: 95%
“…Randomly selected read pairs of 0.25 × coverage for each species were aligned to dimers of the respective satDNA consensus. The abundance was normalized by dividing the total length mapped to each satDNA by the genome length, following Cabral-de-Mello et al ( 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Repetitive sequences are great tools for the study of sex chromosomes, where species with heteromorphic sex chromosomes show a difference in the accumulation of some sequences between males and females, emphasizing the existence of several W/Y-specific satDNAs [ 13 , 14 , 18 , 75 ]. Despite the presence of a well-differentiated X 1 X 2 Y sex chromosome system, minor differences in haplotype accumulation between males and females were observed ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite DNAs (satDNAs) are one of the most common repeated sequences, forming extensive arrays of largely similar repeating units (monomers) that make up a significant percentage of genomes (reviewed in [ 10 ]). Recently, given the integration of cytogenetics with high-throughput sequencing data from next-generation sequencing methods (NGS), the whole collection of different satDNA families (satellitome) of several species has been characterized, providing insights into several evolutionary issues, such as karyotype evolution, genome diversity, and phylogenetic relationships [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These satellites (satDNAs) are also thought to play a role in the evolution and structure of sex chromosomes, as well as chromosome-based speciation [ 13 , 14 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now recognized that tandem repeat DNAs, including microsatellites, minisatellites, and satDNAs, can also be found in euchromatin. Recent studies involving the characterization of satellitome and in situ hybridization with low-abundance satDNA families have revealed that many of these satellite DNA sequences are indeed located in euchromatin (see [68,75] for a review). These findings challenge the traditional view and highlight the presence and distribution of satellite DNA in both heterochromatic and euchromatic regions.…”
Section: Characterization and Chromosomal Localization Of The Main Fa...mentioning
confidence: 99%